INTERCULTURAL COMMUNICATION AS A MEANS OF PERSONALITY FORMATION OF THE FUTURE TEACHER - Myskiv, Iryna (Mountain School of Ukrainian Carpaty, 2021)
The article is devoted to the research of the problem of intercultural communication as a means of the personality formation of the future teacher in the context of modern social factors. This problem is actualized by the fact that changes in the national education system are determined by global, social, domestic, regional and personal aspects. It requires radical changes both in the training of a new generation of professionals capable of understanding and real transformations in modern education at all stages, from preschool to higher educational institutions. The priority areas of educational tasks in terms of reforming and improving the training of future teachers at the present stage include: the formation of a person who realizes their belonging to the Ukrainian nation, accepts and appropriates its values, preserves and multiplies national culture and language; formation of socio-cultural competencies of future teachers, understanding of the importance and complexity of globalization and integration processes; nurturing national and civic values, understanding the difference between them and the role in the life of civilized society; formation of readiness to conduct interethnic and intercultural dialogue, adherence to the position of respect for traditions, culture, religion and language of the peoples of the world; building general didactic, developmental and educational competencies in order to achieve a high level of professional activity. Intercultural communication based on a broad analysis of research is interpreted as a functionally conditioned, communicative interaction of people, who are the carriers of different cultural communities in terms of their awareness of belonging to different geopolitical, continental, regional, religious, national, ethnic communities and social cultures. A special attention in the organization and implementation of intercultural communication is given to the humanities, which are part of the training of future teachers and have significant intercultural potential. They include foreign languages as a means of learning about the world, communication, cultural exchange, etc. The study claims that socio-cultural education and the organization of broad intercultural communication permeates the professional training of teachers and is aimed at developing the cultural, communicative, general pedagogical spheres of future teachers as socially significant actors, carriers and participants in the dialogue of cultures. Language skills, in the broadest sense of the term, become an important competence in every person`s life, especially the one of a teacher who communicates with children and youth and should be a certain role model for their students. Creating conditions for mastering the language and its wide use in everyday life is an important and necessary task of modern education, which should be provided both at the theoretical and applied levels.